Effect of System, Information, and Service Quality and Green IT Attitude Towards User Satisfaction on Clientele ITSM Application Bank XYZ - Muhamad Hafidh Adzhani; Sfenrianto Sfenrianto (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
The banking industry is increasingly shifting toward the advanced use of information technology (IT) to enhance customer service. It is important for the audience to be able to get satisfaction when using banking services. In this case, there are several factors that will impact user satisfaction when using the application. The study's objectives are to examine how system quality affects client satisfaction with the ITSM application at bank XYZ; how user satisfaction with the ITSM application for clients at bank XYZ is impacted by the quality of the information; how client satisfaction with the ITSM application at bank XYZ is impacted by service quality; and how client ITSM application at bank XYZ is impacted by a green IT attitude toward satisfaction. The research employs a quantitative approach, utilizing SEM PLS analysis. The result shows that the system quality has a positive and substantial impact on user satisfaction with a p-value of of 0.021 < 0.05; the information quality has a positive and significant impact on user satisfaction with a p-value of 0.000 < 0.05; the service quality has a negative and significant impact on user satisfaction with a p-value of 0.044 < 0.05; and green attitude has a positive impact on user satisfaction with a p-value of 0.000 < 0.05. The research results indicate that system quality, information quality, and green attitude positively influence user satisfaction, whereas service quality negatively influences it.